Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jvscit.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the inferior vena cava

Abstract: Leiomyosarcoma of the inferior vena cava (IVC) is a rare malignancy. Approximately 350 cases of this disease are known worldwide. Surgical treatment of this condition remains an extremely difficult task. In this case report, we present an experience of successful radical treatment of a leiomyosarcoma of the suprarenal IVC without vascular reconstruction. The patient was treated with resection of the suprarenal portion of the IVC with the tumor; however, in view of adequate blood outflow from the right lobe of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…9 With the developments of cardiopulmonary bypass and the commencement of multidisciplinary collaboration, surgical treatment became feasible. 8,9,11,12 The first resection of the IVC tumor was recorded at Lexington Memorial Hospital in 1951. 10 In 1974, Mandelbaum et al reported the first successful resection of IVC leiomyoma involving right atrium .…”
Section: Discussionmentioning
confidence: 99%
“…9 With the developments of cardiopulmonary bypass and the commencement of multidisciplinary collaboration, surgical treatment became feasible. 8,9,11,12 The first resection of the IVC tumor was recorded at Lexington Memorial Hospital in 1951. 10 In 1974, Mandelbaum et al reported the first successful resection of IVC leiomyoma involving right atrium .…”
Section: Discussionmentioning
confidence: 99%
“…[9] With the developments of cardiopulmonary bypass and the commencement of multidisciplinary collaboration, surgical treatment became feasible. [8,9,11,12] The rst resection of the IVC tumor was recorded at Lexington Memorial Hospital in 1951. [10] In 1974, Mandelbaum et al reported the rst successful resection of IVC leiomyoma involving right atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma is a malignant mesenchymal tumor originating from smooth muscle of gastrointestinal and vascular wall and accounts for 5%-10% of soft tissue tumors [1] . Primary leiomyosarcomas is originated from inferior vena cava (IVC) wall and presents as a very rare clinical entity [2] . It grows slow and insidiously without significant symptoms at early stage; thus, it is extensively advanced with multi-organ and vascular involvement when the diagnosis of leiomyosarcoma is confirmed [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Primary leiomyosarcomas is originated from inferior vena cava (IVC) wall and presents as a very rare clinical entity. [ 2 ] It grows slow and insidiously without significant symptoms at early stage; thus, it is extensively advanced with multi-organ and vascular involvement when the diagnosis of leiomyosarcoma is confirmed. [ 3 , 4 ] With the advancement of surgical oncology and its adjuncts, radical resection has become the only curative option considering poor clinical efficacy of chemo and radio-therapy.…”
Section: Introductionmentioning
confidence: 99%